Uit Vlaanderen - Buysse, Cyriel, 1859-1932 (Salt Lake City, UT : Project Gutenberg, 2015)
"Uit Vlaanderen" by Cyriel Buysse is a novel written in the late 19th century. This work delves into the life and struggles of a working-class family in Flanders, capturing the harsh realities of their existence. The narrative likely centers around the main character, a father who harbors a dream of prosperity, symbolized by the desire to own a pig, which represents both hope and the burden of their social conditions. The opening of the novel introduces us to a sick father who has been bedridden through summer but shows signs of recovery as winter approaches. His long-suffering family prepares for the cold months ahead, and despite their poverty, they cling to the hope of a better future. As the father discusses his lifelong wish to own a pig$1 (Bsomething that would signify wealth and comfort$1 (Bhis family oscillates between despair and fleeting optimism. The opening chapters vividly depict their day-to-day struggles against hunger and cold while foreshadowing the father$1 (Bs relentless yet oftentimes unrealistic dreams for a brighter future, all set against the backdrop of a bleak socio-economic landscape. (This is an automatically generated summary.)s
EEN LEVENSDROOM -- DE PIJPELINGJES -- DE WEDDENSCHAP -- DE GEVANGENEN -- DE KIKKERS -- PIERKE EN KOOTJE -- HET PAARD -- DE DOOP -- DE BAANWACHTER -- DE BROODVERVOERDER -- TRAGEDIE -- DUKSKE.
Release date is 2015-01-19
Produced by Johan Boelaert
Keywords: Essays